The Role of Product Attributes, Brand image, and Celebrity Endorser on Purchase Decision and Their Effects on Consumer Satisfaction on Homypad Shoes Product in Yogyakarta - Sulistiyani, Frans Sudirjo, Honorata Ratnawati Dwi Putranti (International Journal of Advanced Science and Technology, 2020)
This research aims to analyze The Role of Product Attributes, Brand image, and Celebrity endorser on Purchase decisions and their effects on consumer satisfaction on homypad shoes products in Yogyakarta. Type of research is survey research. This research is conducted in Ramayana Mall with research subject consumers who bought Homyped shoes product. Respondents involved in this research are 215 respondents. Data analysis in this research using Structural Equation Modelling (SEM) which is operated AMOS program. Criteria of good and fit model must in accordance with Chi-square, RMSEA, Goodness of Fit Index (GFI), Adjusted Goodness of Fit Index (AGFI), CMIN /DF, TLI (Tucker Lewis Index), and Comparative Fit Index (CFI). Result of research shows that when product attribute (X1) used more interesting and brand image(X2) which attached in the product is better, it will add Purchase decision (Y1) which affect consumer satisfaction (Y2). From celebrity endorser (X3) factor it is not significantly affected the purchase decision (Y1) of consumer and consumer satisfaction (Y2). Purchase decision (Y1) has effect to consumer satisfaction (Y2) because when consumer purchase decision is increased, that will increase consumer satisfaction too.